Society and Democracy in South Korea and Indonesia - Howe, Brendan (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book is divided into three sections comprised of pairs of chapters. First, a section examining how Confucianism interacts with democratic resilience in South Korea, compared with the societal role and challenge of Islam in Indonesian democracy. The second section will conduct brief historical surveys of the role of civil society role in Korean and Indonesian democratization, and debates about the appropriate role for civil society after democratization. In particular, the various roles of civil society non-governmental organizations (NGOs) and popular movements will be highlighted in both countries. The final section looks at socio-economic conditions and distributive justice in relation to democracy in the Republic of Korea (ROK) and Indonesia. Brendan Howe is Dean and Professor of International Relations at Ewha Womans University Graduate School of International Studies, South Korea, and President of the Asian Political and International Studies Association.
1. Political Culture and Societal Exceptionalism: Challenges to Democracy? -- 2. Confucianism and Democracy in South Korea: A Comparative Perspective -- 3. Between the Internal Struggle and Electoral Rules Effect: The Challenges of Political Islam in a Democratic Indonesia -- 4. Civil Society and Democratization in South Korea -- 5. NGOs and Democratization in Indonesia: From Co-optation to Collaboration -- 6. From Post Child to Poor Cousin? Expanding the Frontiers of Economic Democracy in South Korea -- 7. Socio-Economic Conditions and Indonesia Democratic Support -- 8. The Social Basis of East Asian Democracy.
Keywords: Asia-Politics and government; Asian Politics